2017
DOI: 10.2741/4496
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex immunoassays in endometriosis An array of possibilities

Abstract: Multiplex immunoassays range from small-scaled multiplex sandwich ELISAs in a planar or bead-based format to the more expanded antibody arrays employing direct sample labeling. The plethora of data generated from these arrays could be of great interest to understand a complex disorder such as endometriosis. Multiplex immunoassay analysis may provide information on disease pathology and may lead to improved, timely diagnosis. Until now, the use of multiplex immunoassays has been limited in endometriosis. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Recently, Aalamat et al . published a systematic review on the use of multiplex technology for identification of potential novel biomarkers of endometriosis among inflammation associated proteins 42 . They reported that the majority of studies that adapted multiplex technology evaluated potential novel biomarkers of endometriosis in peritoneal fluid 20,31,4347 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Aalamat et al . published a systematic review on the use of multiplex technology for identification of potential novel biomarkers of endometriosis among inflammation associated proteins 42 . They reported that the majority of studies that adapted multiplex technology evaluated potential novel biomarkers of endometriosis in peritoneal fluid 20,31,4347 .…”
Section: Discussionmentioning
confidence: 99%
“…And, with the development of new omics technology and multiple immunoassay techniques, more valuable biomarker panels may be discovered in the near future. [ 59 ]…”
Section: Perspective and Conclusionmentioning
confidence: 99%